Profiles of gene polymorphisms in cytokines and toll-like receptors with higher risk for gastric cancer - De Oliveira, Juliana Garcia [UNESP]; Rossi, Ana Flávia Teixeira [UNESP]; Nizato, Daniela Manchini [UNESP]; Miyasaki, Kenji; Silva, Ana Elizabete [UNESP] (Springer Nature, 2013)
Background: Chronic inflammation and gastric carcinogenesis show a close association, so gene polymorphisms that modify the intensity of the inflammatory response may contribute to variations in gastric cancer risk. Aims: The purpose of this study was to investigate the combined effect of the pro- and anti-inflammatory cytokines and toll-like receptors polymorphisms on the chronic gastritis and gastric cancer risk in a Brazilian population sample. Methods: We evaluated 669 DNA samples (200 of gastric cancer [GC], 229 of chronic gastritis [CG], and 240 of healthy individuals [C]). Ten polymorphisms were genotyped: IL-1RN and TLR2 -196 to -174 del using the allele-specific PCR method and TNF-A (rs1800629; rs1799724), TNF-B (rs909253), IL-8 (rs4073; rs2227532), IL-10 (rs1800872) and TLR4 (rs4986790; rs4986791) using PCR-RFLP. Results: Polymorphisms TNF-A-308G/A, IL-8-251A/T, TNF-B + 252A/G and TLR4 + 1196C/T were not associated with risk of any gastric lesion. However, an association with increased risk for GC was observed for polymorphisms IL-1RNL/2 (p < 0.001), TNF-A-857C/T (p = 0.022), IL-8-845T/C (p < 0.001), IL-10-592C/A (p < 0.001), TLR2ins/del (p < 0.001), and TLR4 + 896A/G (p = 0.033). In CG, an association was observed only with polymorphisms IL-1RNL/2 and IL-10-592A/C (p < 0.001 for both). A combined analysis of these six polymorphisms associated with GC revealed a profile with two to four combined genotypes which confer a higher risk of gastric carcinogenesis, with an OR increased 2.95-fold to 50.4-fold, highlighting the combinations IL-1RN2/TNF-A-857T/IL-8-845C, IL-1RN2/IL-8-845C/TLR2del, IL-1RN2/IL-10-592A/TLR4 + 896G, IL-10-592A/TLR2del/ TLR4 + 896G, and IL-1RN2/TNFA-857T/IL8-845C/TLR2del. Conclusions: Our findings evidenced that the combined effect of polymorphisms in genes involved in the inflammatory process may potentiate the risk of gastric cancer, thus emphasizing the importance of evaluating multiple polymorphisms together. © 2012 Springer Science+Business Media New York.
Keywords: Chronic gastritis; Cytokines; Gastric cancer; Gene polymorphisms; Toll-like receptors; cytokine; interleukin 1 receptor blocking agent; interleukin 10; interleukin 8; lymphotoxin; toll like receptor; toll like receptor 2; toll like receptor 4; tumor necrosis factor alpha; adult; aged; alcohol consumption; Brazil; cancer risk; carcinogenesis; case control study; chronic gastritis; chronic inflammation; controlled study; DNA polymorphism; family history; female; gastric carcinogenesis; gene expression; gene frequency; genetic association; genotype; high risk patient; human; major clinical study; male; polymerase chain reaction; priority journal; restriction fragment length polymorphism; single nucleotide polymorphism; smoking habit; stomach cancer; Adult; Aged; Aged, 80 and over; Case-Control Studies; Female; Genetic Predisposition to Disease; Humans; Interleukins; Male; Middle Aged; Polymorphism, Genetic; Stomach Neoplasms; Toll-Like Receptors; Young Adult